Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India - Ng, Heok Hee (Zootaxa, 2005)
A new species of erethistid catfish, Erethistoides sicula, is described from the Brahmaputra River drainage in northeast India. Erethistoides sicula differs from both E. montana and E. pipri in having a longer caudal peduncle (19.6–22.3% SL vs. 14.4–18.4) and shorter pectoral spine (14.6–28.0% SL vs. 30.7–32.1). It further differs from E. montana in having a dorsally projecting bony splint on the opercle immediately posterior to its articular facet with the hyomandibula (vs. splint absent) and from E. pipri in having a more slender head (13.4–15.1% SL vs. 16.4). The diagnostic characters of Erethistoides are discussed and four new synapomorphies are proposed to diagnose the genus.